Brak obowiązku uzasadnienia i uzasadnienie skrócone a prawo do sądu: [No duty to justify, the shortened justifications and the right to access to the court] (Studia Prawnicze / The Legal Studies, 2014)
The right to fair trial and access to the court is interpreted by European Court of Human Rights in a wide manner. Amongst these rulings, there are numerous judicial opinions, where ECHR addesses the problem of giving grounds for judicial decisions (not mention explicitly in the Convention). Out of that reason we may say that there is possible to notice special element of the general right to due process – right to obtain grounds for judicial decisions. This particular right has many aspects and – at least at the first glance – seems to impose the duty to prepare justifications without exceptions. In practice the situation is yet quite different. ECHR approves some limitations of this duty, that migh arise from different sources. In other words, shortened justifications and lack of the duty to justify may be, under some conditions, compliant with standards set forth by the Convention. The clou of this matter is proportionalization of the justifying process, as well as considering of arguments pro and contra fulfilling maximum standard. Sometimes it is therefore possible that guaranteeing the right to fair trial may be overcome by another values (like promptness of receiving a decision, better governance of judges‘ time and effort, etc.). Considering this issue in a wider perspective, we, hence, cannot try to maximalize one aspects of a standard because, if it may cause obstacles in meeting another elements slocated within it the other rights’ domain.